Análise dos índices de classificação de bovinos avaliados em provas de ganho em peso, em confinamento - MARQUES, Ednira Gleida (2011)
Weight gain performance trials (PGP) in feedlot evaluate the weight gain capacity of the animals, making possible the selection based on phenotypical information. Animals are classified based on pondered indexes for productive traits as average daily weight gain, final weight, type or morphological evaluation, scrotal perimeter, ribeye area and fat thickness. Using data from the Brazilian Association of Zebu Breeders (ABCZ), the aim of this study was to evaluate classification indexes of weight gain performance tests applied to Nellore cattle in feedlot, and to estimate the variance components and the genetic correlations among the traits that compose such indexes. Covariance components and genetic parameters were estimated by the animal model commonly applied in the Restricted Maximum Likelihood Model (REML), using MTDFREML software. Heritability estimates for all traits were medium to high. Genetic correlation estimates were low regarding final weight and average daily weight gain, scrotal perimeter and carcass traits. Final weight, ribeye area, average daily weight gain and fat thickness were considered medium. Therefore, major genetic gain can be obtained when using selection indexes aimed at final weight